Above Pekel med vodami toward Mohokos, Železna gora and Per(n)jak - Bajuk, Lidija (Poznańskie Studia Slawistyczne, 2012)
I conducted my own ethnographic field research in 1998, 2004 and 2007. Further field research, from 2010 to 2012, under the title ‘Folk Piety and the Transmission of Ethnoheritage in Upper Meñimurje’, was part of Tomo Vinšćak’s academic project Sacral Interpretation of Landscape, organized by the Matapur Association and the Ethnological and Anthropological Department of the Faculty of Philosophy in Zagreb. The analysis and comparison of the collected materials has contributed to research into the fascinating and still vibrant – though under-researched – survival strategies of pre-Christian and Christian worldviews in the western and north-western parts of the northernmost districts of Croatia.